HUBUNGAN KEPATUHAN MINUM OBAT HIPERTENSI DENGAN TINGKAT KEKAMBUHAN PADA LANSIA YANG MENGALAMI HIPERTENSI DI PUSKESMAS OESAPA KOTA KUPANG - Mersy Toh mey; Erna Febriyanti Erna Febriyanti; Balbina Antonelda M Wawo (Citra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2021)
Hypertension is one of the big problems in the elderly (elderly) because it is often found and is a major factor in the occurrence of heart problems and coronary heart disease which is very dangerous. The purpose of this study was to determine the relationship between adherence to taking hypertension medication with recurrence rates in elderly people with hypertension at the Oesapa Health Center, Kupang City. The research method used is quantitative research with a cross-sectional approach. The sample in this study were 97 elderly in Oesapa Community Health Center Kupang City who were selected using inclusion criteria and using purposive sampling technique. Data collection using a questionnaire. The results showed that of the 31 respondents who had adherence to taking medication in the non-adherent category with a recurrence rate of 1 person (1.0%) and in the relapse category as many as 30 people (30.9%). Meanwhile, of the 66 respondents who had adherence to taking medication in the obedient category there were 64 people (66.0%) with a recurrence rate in the relapse category of 2 people (2.1%), the results of further statistical tests obtained p value = 0.000 ( at α <0.05) which means that there is a significant relationship between adherence to taking hypertension medication with the recurrence rate. It is hoped that elderly patients who have a history of hypertension continue to take medication so that blood pressure does not increase and there are recurrences and complications that continue and it is hoped that the family or employees will take medication to remain active so that the elderly can control blood pressure. Keywords: Compliance with Hypertension Medication, Recurrence Rate.